Impact of COVID-19 on Pregnant Women and Maternity Nurses. Issue 4 (July 2021) - Simpson, Kathleen Rice
Abstract : There have been many changes in maternity care due to the COVID-19 pandemic that have affected pregnant women and nurses, some of which will continue long after the pandemic is under control. These practice changes warrant study and we welcome manuscripts about these important topics.